Theoretical principles and criteria of historical and genetic differentiation of lexical parallels between Turkiс and Mongolian languages - Utebekov, Senbek; Koç, Kenan (The New Research of Tuva, 2025)
In this article, we analyze the problems related to the theory of Altaic languages and lexical parallels between them. For this purpose, new findings and information in the work of the Kazakh linguist Janseyit Tuymebayev “Principles and Criteria of Historical and Genetic Differentiation of Lexical Parallels of Turkic and Mongolian Languages” published in 2024 are taken as a basis. In the Introduction section of the article, the historical development of the theory of Altaic languages and information about Tuymebayev’s other works on the Altaic theory are presented. In the main part, the researcher’s studies in the field of Altaistics to date, his opinions put forward, the historical and cultural contacts between the Turkic and Mongolian peoples, the results of their linguistic interactions, the evaluations and determinations on the historical development processes of cultural contacts between the languages in question are considered scientifically. In addition, Tuymebayev’s information about the linguistic features and vocabulary of Tuvan, which is more affected by Mongolian when compared to other Turkic dialects, and the similarities of Mongolian elements in Kazakh in terms of meaning and sound are analyzed.
Keywords: Altaic languages; Turkiс languages; Mongolian languages; Janseyit Tuymebayev; cultural borrowing; cultural relation; lexical parallel